Delafossite type CuCo0.5Ti0.5O2 composite structure: A futuristic ceramics for supercapacitor and EMI shielding application. Issue 7 (1st April 2021) - Bhattacharya, Debopriya; Ghoshal, Debopriyo; Mondal, Dheeraj; Paul, Biplab Kumar; Pal, Joydeep; Gupta, Bhaskar; Bose, Navonil; Nandy, Papiya; Basu, Mousumi; Das, Sukhen
Abstract: Cu-based delafossite type CuCo0.5 Ti0.5 O2 composite structure has been synthesized via a simple chemical synthesis technique followed by a high-temperature sintering process. Structural investigations on the synthesized sample have been carried out by using XRD, FT-IR, and Raman spectroscopy techniques. Optical spectroscopy (UV–Vis and photoluminescence) study reveals beneficial information about the bandgap (Eg ) and defect state density of CuCo0.5 Ti0.5 O2 composite structure, explaining the superior electrochemical and microwave shielding performance of the composite structure. Cyclic voltammetry and galvanostatic charge-discharge measurement within the potential window of −0.5 V to +0.4 V illustrate the pseudocapacitive nature of the sample with a specific capacitance value of 283 F g -1 at a current density of 0.5 A g -1 which can retain up to 86% of its original value after 2000th cycle. A 400 μm thin sample made of CuCo0.5 Ti0.5 O2 composite structure is capable to shield up to 58 dB of incident electromagnetic (EM) wave energy at 16.5 GHz wavelength with absorption efficiency of 52.5 dB. The electromagnetic interference (EMI) shielding effectiveness (SE) is found to be 99.999% against the harmful electromagnetic interference in the 8–12 GHz frequency region.